Hablon weaving by the Indag-an primary multi-purpose cooperative in Miag-ao, Iloilo (1991-2005). - Muralla, Jhoan N
The study, "Hablon Weaving by the Indag-an Primary Multi-Purpose Cooperative in Miag-ao (1991-2005), focuses mainly on the operation of the Indag-an Primary Multi-Purpose Cooperative as the center of the hablon weaving in Miag-ao and the establishment of the cooperative. It discusses the cooperative's weavers, production and marketing and specific problems and solutions applied., The assistance given by the local and national governments for the improvement of the said insdustry is aslo determined. Furthermore, the study discusses the contributions of the hablon weaving industry to Barangay Indag-an and to Miag-ao as a whole. Hablon weaving serves as source of income among families in Barangay Indag-an and promote tourism and popularity of the town and the barangay. The presence of the hablon center in Barangay Indag-an somehow contributed to the reconstruction of the Malagyan-Banbanan road. Some recommendations are advanced for the further improvement of the hablon weaving. The government should take part in the marketing of the hablon products. Brochure is recommended for a better promotion of the cooperative's hablon weaving and its finished products. Schools and other institutions in Miag-ao should help in patronizing hablon through using it as office or school uniforms. Trainings and semianrs are highly suggested to be held in Miag-ao or in the cooperative for the weavers to have a big chance to develop their skill and craftmanship. Young generation should also encouraged to be engaged and have interest in hablon weaving . Data were gathered through interviews with the cooperative's manager, weavers, and local officials and through library research. Photos are utilized for documentation and to better understand the materials, processes and finished products of hablon weaving.